2020
DOI: 10.1002/fsn3.1512
|View full text |Cite
|
Sign up to set email alerts
|

Aquaponics production of catfish and pumpkin: Comparison with conventional production systems

Abstract: Aquaponics is known to be a smart way of producing fish and crops simultaneously; however, there is a paucity of information about the extents of this system's efficiency over other conventional methods of food production. Thus, this study was designed to evaluate the performance of a catfish–pumpkin aquaponics system in comparison with recirculatory and static aquaculture systems (for fish performance), as well as irrigated and nonirrigated systems (for pumpkin performance). Results obtained showed that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
3
10
0
2
Order By: Relevance
“…However, the high correlation between weight and length in both fish tanks indicated a highly positive relationship between these parameters across the fish tanks. These results corroborate several other studies (Atique et al, 2022;Obirikorang et al, 2021;Oladimeji et al, 2020) that reported improved weight of fish raised in aquaponics compared to those raised in conventional fishponds.…”
Section: Clarias Gariepinus Gained More Biomass In the Aquaponicssupporting
confidence: 92%
See 1 more Smart Citation
“…However, the high correlation between weight and length in both fish tanks indicated a highly positive relationship between these parameters across the fish tanks. These results corroborate several other studies (Atique et al, 2022;Obirikorang et al, 2021;Oladimeji et al, 2020) that reported improved weight of fish raised in aquaponics compared to those raised in conventional fishponds.…”
Section: Clarias Gariepinus Gained More Biomass In the Aquaponicssupporting
confidence: 92%
“…Mortality observed in the control fish tank may be due to shocks introduced by the regular complete water-changing regime, which might lead to disruption of osmoregulation and functional metabolism. (Oladimeji et al (2020) reported a significant improvement in the survival rate of C. gariepinus raised in pumpkin aquaponics compared to that of the control. The high mortality rate of C. gariepinus is a major source of revenue for farmers(Fernández Sánchez et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…Limo a 1 dS m -1 , y está de acuerdo con la NOM-021- SEMARNAT-2000(SEMARNAT, 2002. En otro estudio en donde se evaluó un suelo irrigado con aguas residuales acuícolas de manera continua, se reportó un pH de 5,55 y una conductividad eléctrica de 2,71 dS m -1 , superior a la que se tuvo en los suelos bajo estudio, lo que va a depender de la biomasa presente, el tipo de producción y del manejo de la unidad de producción acuícola, así como al suelo (Oladimeji et al, 2020).…”
Section: Materia Orgánicaunclassified
“…Providing information on the production of South American species in aquaponics systems can encourage the implementation of these systems, and therefore help to minimize the continent's problems related to high-quality food supply and the pressure on natural resources. Compared to cage and pond-based aquaculture systems, both recirculating aquaculture systems (RAS) and aquaponics need lower volumes of water and smaller areas of land to produce fish (Oladimeji et al 2020;Lennard and Goddek 2019;Martins et al 2010). In aquaponics, some of the negative effects of fish production, such as nutrient-rich effluent discharge, can be reduced through nutrient reuse by plants and energy/nutrient recovery after waste treatment by implementing additional technologies (Goddek et al 2019a).…”
Section: Introductionmentioning
confidence: 99%